Slam – en outnyttjad resurs i skogsbruket - Mikael, Sörhult; Olof , Högqvist (2010)
Every year about 210 000 tones dry weight of sewage sludge is produced in Sweden. Most of the sludge is applied to agricultural land, plantsoil and landfill cover. Sewage sludge contains essential nutrients such as nitrogen and phosphorus. Nitrogen is limiting growth on solid ground in Sweden and can therefore be used as fertilizer to increase productivity. In order that the sludge can be spread to forest land it requires first a conversion of sludge to pellets, to make it more manageable. Sludge contains in average of four percent nitrogen. In order to get the same application amount of nitrogen as for mineral fertilizers about seven times more sewage sludge has to be applied to the land. The problem is that the sludge contains organic pollutants and heavy metals. Sewage sludge also contains pathogens, but they are killed efficiently when the sludge is converting to pellets. It is possible to use sludge pellets as an alternative to mineral fertilization. Of a total of 6780 hectares in Krycklan is possible to fertilize 1748 according the Forest Agency guidelines for nitrogen fertilization and seven demands.